Comparing Data of Occupational Accidents, Existing Problems and Solution Recommendations - GÜL, Ömer Faruk; Özçoban, Nurettin Oğuzhan; Aydoğan, Fatih (Turkey Health Literacy Journal, 2021)
The number of accidents at work in Turkey has increased significantly in recent years. The total number of occupational accidents in 2019 was 1.75 times that of 2015. Work-related deaths have also increased with the increase in work accidents. In addition to the production equipment and environmental conditions, many technological, sociological, psychological and physiological factors play a role in the occurrence of occupational accidents. Focusing on these factors and improving working conditions is important to prevent accidents and injuries. The effects of occupational accidents are not limited to the physical and mental health of the workers. Accidents also negatively affect the worker's social environment, employer and co-workers. Therefore, the measures taken against work accidents also reduce the burden of financial and social problems caused by these accidents. The concept of Occupational Safety and Health(OSG), which was born in order to solve current problematic situations, has become a guide for this road map. If this road map required to prevent occupational accidents is not drawn and OSH measures are not taken, the continuity of occupational accidents will be inevitable and the consequences will be negative financially and morally. Therefore, in order to take necessary and up-to-date measures against occupational accidents and injuries, a road map should be drawn by making use of data from other countries and comparing them.
Keywords: Occupational health; occupational Safety; occupational accident; Occupational Safety and Health (OSH); working environment